Water quality of Barishal sadar upazila in Bangladesh for drinking, irrigation, aquaculture and livestock consumption (Asian Journal of Medical and Biological Research, 2020)
A study was conducted to assess of groundwater and surface water quality of Barisal sadar upazila. Total 22 water samples (11 pond water and 11 groundwater) were collected from January to March, 2017. Samples were slightly acidic in nature and 7 pond water not suitable for aquaculture in respect of pH. Samples of pond were “excellent” and groundwater samples were “good” for irrigation except two high salinity group water for irrigation for EC. Calcium indicates the samples were suitable for aquaculture but 7 samples were not suitable due to higher Mg content. In respect of K, 9 samples were not suitable for aquaculture. Cu concentrations found suitable for all purposes. For Fe and Zn samples are suitable for irrigation and consumption. Chloride showed, samples were not suitable for livestock consumption except 7 ponds sample. Samples are not suitable for aquaculture in respect of Cl, Fe and Zn. For Manganese, samples (except 1) found suitable for consumption. Samples were “excellent” for sensitive, semi-tolerant and tolerant crops in respect of B. Not any samples responded to CO3 test and HCO3 concentrations found normal. All water sources free from Arsenic contamination. Phosphorus concentration in groundwater might not be harmful for multipurpose use. SAR categorized all samples “excellent” class for irrigation except 2 groundwater samples. 15 samples were “suitable”, 3 were “marginal” and 4 were “unsuitable” for irrigation in respect of RSC. For HT, 13 were “moderately hard” and 09 were “hard” limit for irrigation and samples were suitable for drinking and livestock consumption.Asian J. Med. Biol. Res. March 2020, 6(1): 44-55